RISK ASSESSMENT OF MAHIGA AND GUADALUPE RIVERS OF METRO CEBU, PHILIPPINES - Alburo, Rosalyn; Villegas, Lora Mae; Cabanag, Fraulein (Journal of Agriculture and Technology Management, 2018)
Two prominent urban rivers in Metro Cebu namely, Mahiga and Guadalupe were sampled and analyzed in situ using a Multi-probe digital meter for their physico-chemical properties like pH, dissolved oxygen and temperature while linear alkyl benzene sulfonates (LAS) and ammonia were determined colorimetrically using UV-VIS spectrophotometer. Metal concentrations of the water samples were also analyzed using Ion-Coupled Plasma (ICP) Spectroscopy. The results of the study revealed that only Guadalupe River met the Department of Environment and Natural Resources Administrative Order 34 (DENR-DA 34, 1990) standard limit of 5 ppm for dissolved oxygen. Mahiga river failed both the DENR-DAO 34 and Environmental Protection Agency (EPA, 2012) standard for NH3 which is 0.50 ppm and 0.20 ppm, respectively. Further, the elevated LAS values were consistent with the high phosphorus concentrations in Mahiga and Guadalupe. The PEC/PNEC or Risk Quotients revealed that the urban rivers under study were at possible risk  implying the need for immediate intervention to rehabilitate and save the river systems. Large scale environmental rish assessment is highly recommended.